National Action Towards a World Free of Cervical Cancer for All Women. Issue 11 (November 2021) - Torode, Julie; Kithaka, Benda; Chowdhury, Raveena; Simelela, Nothemba; Cruz, Jennifer L.; Tsu, Vivien D.
Abstract : (Abstracted from Prev Med 2021;144:106313) Cervical cancer is a preventable disease that continues to have an annual incidence of nearly 600, 000 cases with disproportionate disease burden and death occurring in marginalized populations and low- and middle-income countries. Evidence suggests that elimination of cervical cancer as a public health problem is more feasible than it has ever been, and that the incidence can be brought below 4 per 100, 000 women globally within a century.